MgAl2O4 ceramics doped with rare earth ions: Synthesis and luminescent properties; AIP Conference Proceedings; Vol. 2174 : Physics, Technologies and Innovation (PTI-2019) - Valiev D. T. Damir Talgatovich; Khasanov O. L. Oleg Leonidovich; Stepanov S. A. Sergey Aleksandrovich; Dvilis E. S. Edgar Sergeevich; Paygin V. D. Vladimir Denisovich (2019, 2019)
Title screen